An evaluation study of the application of educational integration in the governorates of Latakia and Hama (Journal of Hama University, 2025)
The research aimed to evaluate educational integration in the governorates of Latakia and Hama, compare the application of educational integration between them, and identify the proposals of the educational integration coordinators in the two directorates of education in the two previous governorates to advance the reality of educational integration. To reach these goals, the researcher adopted the interview as a research tool that was applied to the two educational integration coordinators in The directorates of education in Latakia and Hama, following the comparative approach, and the results confirmed the existence of many points of similarity between the two research governorates in the application of educational integration, with some points of difference such as the number of inclusive schools and the number of students with disabilities who benefit and teachers included in following training courses related to educational integration at the level The two search governorates.
Keywords: The Evaluation, Educational integration, Inclusive schools.